2016
DOI: 10.1177/0954405415590560
|View full text |Cite
|
Sign up to set email alerts
|

Turning by electrical discharge machining: A review

Abstract: Turning by electrical discharge machining is an emerging area of research. Generally, wire-cut electrical discharge machining is used for turning because it is not concerned with electrode tooling cost. The process variant die-sinking electrical discharge machining can also be effectively used to generate free-form cylindrical geometries on difficult-to-cut materials with complex shapes at both macro and micro levels. The machining performance of electric discharge machine is defined and influenced by its proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 93 publications
(115 reference statements)
0
13
0
1
Order By: Relevance
“…The process variants in die-sinking EDM can be fine-tuned to generate free-form cylindrical geometries on difficult-to-cut materials at both macro- and micro levels. Gohil and Puri 89,90 carried out work in the area of ED turning for the improvement of MRR, surface integrity and roundness. In this review, various techniques reported by EDM researchers on turning have been categorized in different EDM variants.…”
Section: Current Development Trend In Micro-edmmentioning
confidence: 99%
See 1 more Smart Citation
“…The process variants in die-sinking EDM can be fine-tuned to generate free-form cylindrical geometries on difficult-to-cut materials at both macro- and micro levels. Gohil and Puri 89,90 carried out work in the area of ED turning for the improvement of MRR, surface integrity and roundness. In this review, various techniques reported by EDM researchers on turning have been categorized in different EDM variants.…”
Section: Current Development Trend In Micro-edmmentioning
confidence: 99%
“…Different techniques adopted for EDM turning process. 89 Research gaps and challenges in the micro-EDM of difficult-to-machine materials (Ti6Al4V, nickel sheet and stainless steel)…”
Section: Current Development Trend In Micro-edmmentioning
confidence: 99%
“…24 Based on the type of the response characteristics, Taguchi categorized response characteristics into three special types, such as the-higher-the-better (HB), the-nominal-the-better (NB) and the-lower-the-better (LB). In this study, HB is considered to maximize the MRR and LB is considered to minimize the surface roughness, and for such class, S/N ratio is expressed as in equations (5) and (6), respectively (HB)h = À 10 log 1 n…”
Section: S/n Ratio Analysismentioning
confidence: 99%
“…4 One of the main industrial applications of die sinking EDM machine is especially in turning aerospace honey-comb seals where the internal and external seals are machined to a bur-free finish with the internal and external diameters from 300 to 1400 mm. 5 Example of a machined part using EDT method is shown in Figure 3.…”
Section: Introductionmentioning
confidence: 99%
“…2 shows a precise rotary spindle setup which was added to the conventional EDM machine to give rotary motion to the workpiece. A die-sinking EDM machine is widely used for turning aerospace honey-comb seals where internal and external seals are machined to a burr-free finish with internal or external diameters from 300mm-1400mm [3][4][5][6]. An example of a machined part produced by the EDT method is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%